A landscape survey of planned SMART/HL7 bulk FHIR data access API implementations and tools. (1st March 2021) - Jones, James; Gottlieb, Daniel; Mandel, Joshua C; Ignatov, Vladimir; Ellis, Alyssa; Kubick, Wayne; Mandl, Kenneth D
Abstract: The Office of National Coordinator for Health Information Technology final rule implementing the interoperability and information blocking provisions of the 21st Century Cures Act requires support for two SMART (Substitutable Medical Applications, Reusable Technologies) application programming interfaces (APIs) and instantiates Health Level Seven International (HL7) Fast Healthcare Interoperability Resources (FHIR) as a lingua franca for health data. We sought to assess the current state and near-term plans for the SMART/HL7 Bulk FHIR Access API implementation across organizations including electronic health record vendors, cloud vendors, public health contractors, research institutions, payors, FHIR tooling developers, and other purveyors of health information technology platforms. We learned that many organizations not required through regulation to use standardized bulk data are rapidly implementing the API for a wide array of use cases. This may portend an unprecedented level of standardized population-level health data exchange that will support an apps and analytics ecosystem. Feedback from early adopters on the API's limitations and unsolved problems in the space of population health are highlighted.